(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This paper explores the integration of Python into computer science education, highlighting its benefits due to Python’s simplicity and extensive applicability across various technological fields. Python facilitates an engaging learning environment through its clear syntax and robust libraries, making it ideal for both introductory and advanced programming lessons. The discussion includes Python’s role in enhancing teaching methods, supporting hands-on learning, and preparing students for future technological careers. This approach not only improves students’ understanding of programming concepts but also equips them with valuable skills for the digital age.